Curve and surface modeling with constrained b-spline wavelets. - Awang, Mohd Nain (Universiti Sains Malaysia, 2011)
The main purpose of this paper is the visualization of convex surface data to present a smooth. visually pleasing and interactive convexity preserving surfaces. The rational cubic function with three free parameters is extended to rational bi-cubic partially blended function to preserve the shape of convex surface data. The function involves twelve free parameters in each rectangular patch. Data dependent constraints are derived for four of these parameters to preserve the shape of convex surface data while other eight are left free to user for the refinement of convexity preserving surface of data. Moreover, the scheme under discussion is C, flexible, simple, local and economical as compared to existing schemes.